The Financial Times Guide to Inclusion and Diversity - Leach, Vikki (The FT Guides, 2021)
87% of companies state I&D is a value or priority area for them, but only 10% of I&D programmes are fully mature. This is even though research shows that organisations with an inclusive culture perform better, are more innovative and agile, and achieve better business outcomes. Written by a respected I&D expert, The FT Guide to Inclusion and Diversity shows you everything you need to know about how to create and implement a I&D strategy that will have a positive impact on people performance and business results. This book gives you a step-by-step guide to the tools, theory and the latest new thinking you need to design a compelling I&D strategy for your organisation. Clear, compelling and comprehensive, this book is designed for leaders and executives to ensure they can bring talented people together from different backgrounds and thinking, creating greater success and benefits to business performance and profitability. This book takes you through a fair and equal approach developed specifically for senior business leaders. It will help you: Design and implement a I&D strategy that will have a positive impact on performance and results. Recognize the value of inclusion and diversity and how it can impact clients positively as well as the organization. How to link the I&D strategy to your wider business goals and set metrics to check its return on investment. Learn techniques on how to drive I&D through your organization and articulate why it is critical to employees. Elect executive sponsors to ensure commitment is demonstrated from the top.